Genetic association study of TERT gene variants with chronic kidney disease susceptibility in the Chinese population - Yan Su; Yuan Feng; Xinran Lin; Chunyang Ma; Jiali Wei (Renal Failure)
The incidence and mortality of chronic kidney disease (CKD) are increasing globally. Studies have demonstrated the significance of genetic risk factors in the progression of CKD. Telomerase reverse transcriptase (TERT) may be implicated in the development of CKD. This study aimed to investigate the correlation between TERT gene variants and susceptibility to CKD in the Chinese population. A total of 507 patients with CKD and 510 healthy controls were recruited for this case-control study. Four candidate loci were identified using the MassARRAY platform. Logistic regression analysis was employed to assess the association between TERT gene variants and the risk of CKD. The false positive reporting probability (FPRP) method was utilized to evaluate the validity of statistically significant associations. The multifactorial dimensionality reduction (MDR) method was used to evaluate the interaction between SNPs and the risk of CKD. Furthermore, discrepancies in the clinical features of subjects with diverse genotypes were evaluated using one-way analysis of variance (ANOVA). Our findings revealed a correlation between rs2735940 and rs4635969 and an increased risk of CKD. Stratification analysis indicated that rs4635969 was related to an increased risk of CKD in different subgroups (age ≤ 50 years and male). MDR analysis indicated that the two-site model (rs2735940 and rs4635969) was the best prediction model. Furthermore, the rs2735940 GG genotype was found to be linked to an increased level of microalbuminuria (MAU) in patients with CKD. Our study is the first to reveal a connection between TERT gene variants and susceptibility to CKD, providing new insights into the field of nephrology.